Integrative 3D recording methods of historic architecture: Burg Hohenecken castle from southwest Germany - Pattee, Aaron; Höfle, Bernhard; Seitz, Christian (IEEE Xplore digital library, 2015)
This paper explores the methodology and application of laser scanning and photogrammetric recording methods to a very complex castle ruin. These methods allow for exact measurements to be made and the production of 3D digital models of the structure in question. The models built from the respective data combine the measuring strength of laser scanning with the visual aesthetics of photogrammetry. The case study is the medieval castle Burg Hohenecken in the city of Kaiserslautern in southwest Germany. Once digitized as a 3D model, the castle can be virtually controlled and examined, providing an opportunity to determine the age and potentially to reconstruct the castle from the different periods of it construction and expansion. Future analyses will include the identification of the different stone types and ages from the different building phases, the viewsheds from each respective building phase and perhaps the discovery of structures which have been completely lost.
Gesehen am 22.05.2025
In: 2015 Digital Heritage